Willingness to pay a high-premium for fresh organic produce: an econometric analysis - Ramu Govindasamy; Surendran Arumugam; Isaac Vellangany; Burhan Ozkan (Agricultural Economics Research Review, 2023)
This paper aims at predicting characteristics of the buyers who are willing to pay (WTP) a high-premium for organic fruits and vegetables in the mid-Atlantic region of US. The results indicate that those who are Caucasian, have a graduate degree and income above $100,000/annum, use advertisements, prefer certified labels, frequently buy at direct markets, think organic food has better taste, switch supermarkets to buy organic produce, prefer processed organic foods are more likely to pay a highpremium. While, those who regularly shop at more than one food store, are influenced by the naturally grown label, prefer conventionally grown local produce and consider buying organic food is a waste of money are less likely to pay a high-premium for organic fresh fruits and vegetables. These findings provide essential feedback to producers of organic produce in targeting customers for sale of organic products.